Safety pharmacology of acute LSD administration in healthy subjects - Holze, Friederike; Caluori, Toya V.; Vizeli, Patrick; Liechti, Matthias E. (Psychopharmacology, 2022)
Rationale Lysergic acid diethylamide (LSD) is used in psychiatric and psychological research and investigated as a potential treatment for medical and psychiatric disorders, including depression, anxiety, and cluster headache. Objectives Safety data on clinical safety are available from small studies but not from larger samples. We report safety pharmacology data from a large pooled study sample on acute effects of LSD in healthy subjects. Methods We conducted a pooled analysis of four double-blind, randomized, placebo-controlled, crossover studies that included a total of 83 healthy subjects and 131 single-dose administrations of LSD. LSD administrations were matched to dose groups according to measured LSD peak plasma concentrations to adjust for uncertainties in the correct LSD dose in some studies. Single doses were 25, 50, 100, and 200 µg of LSD base. We investigated subjective effects (self-rated any drug effect, good drug effect, bad drug effect, and anxiety), blood pressure, heart rate, body temperature, duration of the acute LSD response, acute (12 h) and subacute (24 h) adverse effects, reports of flashbacks, and liver and kidney function before and after the studies. Results LSD dose-dependently increased subjective, physiologic, and adverse effects. The dose–response curves for the proportions of subjects with a certain amount of a subjective effect were steeper and reached a higher maximum for positive acute subjective effects compared with negative acute subjective effects. Maximal ratings of > 50% good drug effects were reached in 37%, 91%, 96%, and 91% of the LSD administrations at 25, 50, 100, and 200 µg. Maximal ratings of > 50% bad drug effects were reached in 0%, 9%, 27%, 31% at 25, 50, 100, and 200 µg, respectively. Mean ratings of Oceanic Boundlessness were 10%, 25%, 41%, and 44%, and mean ratings of Anxious Ego-Dissolution were 3.4%, 13%, 20%, and 22% at 25, 50, 100, and 200 µg, respectively. The physiologic effects of LSD were moderate. None of the subjects had systolic blood pressure > 180 mmHg at any time. Peak heart rate > 100 beats/min was observed in 0%, 6%, 20%, and 25% of the subjects at 25, 50, 100, and 200 µg, respectively. Maximal heart rates of 129 and 121 beats/min were observed in one subject at the 50 and 200 µg doses, respectively. Peak body temperature > 38° was observed in 0%, 11%, 7%, and 34% at 25, 50, 100, and 200 µg, respectively. Mean acute adverse effect scores on the List of Complaints were 5.6, 9.2, 12, and 13 at 25, 50, 100, and 200 µg, respectively. Kidney and liver function parameters were unaltered. Six subjects reported transient flashback phenomena. Conclusions The single-dose administration of LSD is safe in regard to acute psychological and physical harm in healthy subjects in a controlled research setting.